ANALISIS INVESTASI, INFLASI, INDEKS PEMBANGUNAN MANUSIA, TERHADAP LAJU PERTUMBUHAN EKONOMI PERIODE 2005-2021 - Muhammad Rafi; Cep Jandi Anwar (Transformasi: Journal of Economics and Business Management, 2022)
Investment is important part of development economic, especially on increase of economic growth. Through investment, various of production facilities will be provide, thus will give optimally production output and value added, as a result can improve the economic growth. Invesment activities can be done by two main sectors, government and private. Majority of government investment commonly to finance physical and non-physical development that could not be conducted by society. Lack of capital in government sector influence low of encourage on physical infrastructure as driving of business and economic activieis. That condition will impact on private investment. This study will explain the effect of investment variables and another economic variables, such as economic growth, human development index, inflation in Indonesia.